Analisis Faktor Yang Mempengaruhi Minat UMKM Dalam Menyusun Laporan Keuangan Sesuai SAK EMKM - Andika Dwi Krisna; Purwanti, Lilik (Telaah Ilmiah Akuntansi dan Perpajakan, 2023)
This study aims to examine empirically the effect of business background, business scale, and MSME entrepreneurs’ perspective of income tax on the intention of MSME entrepreneurs to prepare financial reports based on FAS for MSME. The samples in this study involve the MSME entrepreneurs with FAS for MSME knowledge in Lumajang District. The effect of independent variables on the dependent variables is examined through multiple regression analysis utilizing SPSS software. The results of this study indicate that the business background and perspective of MSME entrepreneurs on income tax have a significant effect on the intention of MSME entrepreneurs to prepare financial reports based on FAS for MSME, while business scale does not affect the intention of MSME entrepreneurs to prepare financial reports based on FAS for MSME.